2015
DOI: 10.1002/jrs.4780
|View full text |Cite
|
Sign up to set email alerts
|

On‐site detection of phosgene agents by surface‐enhanced Raman spectroscopy coupled with a chemical transformation approach

Abstract: Phosgene and its analogs are greatly harmful to the public health, environmental safety and homeland security as widely used industrial substances with extremely high toxicity. In order to rapidly evaluate the emergency risk caused by these chemicals, a new highly sensitive method based on surface-enhanced Raman spectroscopy (SERS) technique for measurement of phosgene agents was developed for the first time. Coupled with a chemical transformation approach, the highly toxic phosgene was conveniently converted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…Gao et al demonstrated the on‐site detection of phosgene agents by SERS coupled with a chemical transformation approach. This work is the first report of SERS measurement on phosgene and diphosgene at a quantitative level . Gu and Lu described Raman mode‐selective spectroscopic imaging of coenzyme and enzyme redox states of FMN nitric oxide synthase using SERS, and they demonstrated consistency with the results of spectral calculations using DFT .…”
Section: Surface‐enhanced Raman Spectroscopysupporting
confidence: 52%
See 1 more Smart Citation
“…Gao et al demonstrated the on‐site detection of phosgene agents by SERS coupled with a chemical transformation approach. This work is the first report of SERS measurement on phosgene and diphosgene at a quantitative level . Gu and Lu described Raman mode‐selective spectroscopic imaging of coenzyme and enzyme redox states of FMN nitric oxide synthase using SERS, and they demonstrated consistency with the results of spectral calculations using DFT .…”
Section: Surface‐enhanced Raman Spectroscopysupporting
confidence: 52%
“…This work is the first report of SERS measurement on phosgene and diphosgene at a quantitative level. [30] Gu and Lu described Raman mode-selective spectroscopic imaging of coenzyme and enzyme redox states of FMN nitric oxide synthase using SERS, and they demonstrated consistency with the results of spectral calculations using DFT. [31] Hernandez et al used SERS to study the anti-inflammatory drug piroxicam adsorbed on the surface of silver or gold colloids as nanocarrier model.…”
Section: Theoretical Aspects Of Sers Enhancementmentioning
confidence: 68%
“…Taranenko and co-workers reported the analysis of nerve agents dimethyl methylphosphonate (DMMP, a sarin derivative) and diisopropyl methylphosphonate (DIMP) using silver electrodes . A dosimeter was developed for the rapid detection of chemicals without the need for sample collection and extraction. , Gao et al proposed a chemical transformation of phosgene agents into the less toxic iodine (I 2 ) respecting stoichiometric proportions, followed by quantitation by silver nanoparticles SERS …”
Section: Other Forensic Related Fieldsmentioning
confidence: 99%
“…211,213 Gao et al proposed a chemical transformation of phosgene agents into the less toxic iodine (I 2 ) respecting stoichiometric proportions, followed by quantitation by silver nanoparticles SERS. 214 Fire Accelerants. Fire debris detection and analysis presents a challenge on fire scenes due to the extreme degradation and temperatures that occurred.…”
Section: ■ Other Forensic Related Fieldsmentioning
confidence: 99%
“…Herein, we developed a new surface-enhanced Raman spectroscopy (SERS) method to address the analytical problems and realized a rapid and highly sensitive detection on SUX to meet the demand of first aid, emergency response, and forensic investigation. The application of SERS techniques in rapid, on-site detection of clinical common toxicants is increased rapidly, for example, directed detection on hydrogen cyanide, [17] amphetamine, [18] codeine, [19] and paraquat, [20] and indirect detection on organophosphorus pesticide [21] and phosgene [22] by the chemical transformation approach. The goal of this work is to achieve highly sensitive and selective SERS measurement of SUX in aqueous solution, as well as in plasma and urine.…”
Section: Introductionmentioning
confidence: 99%